A draft genome of the honey bee trypanosomatid parasite Crithidia mellificae. - Charles Runckel; Joseph DeRisi; Michelle L Flenniken (PLoS ONE, 2014)
Since 2006, honey bee colonies in North America and Europe have experienced increased annual mortality. These losses correlate with increased pathogen incidence and abundance, though no single etiologic agent has been identified. Crithidia mellificae is a unicellular eukaryotic honey bee parasite that has been associated with colony losses in the USA and Belgium. C. mellificae is a member of the family Trypanosomatidae, which primarily includes other insect-infecting species (e.g., the bumble bee pathogen Crithidia bombi), as well as species that infect both invertebrate and vertebrate hosts including human pathogens (e.g.,Trypanosoma cruzi, T. brucei, and Leishmania spp.). To better characterize C. mellificae, we sequenced the genome and transcriptome of strain SF, which was isolated and cultured in 2010. The 32 megabase draft genome, presented herein, shares a high degree of conservation with the related species Leishmania major. We estimate that C. mellificae encodes over 8,300 genes, the majority of which are orthologs of genes encoded by L. major and other Leishmania or Trypanosoma species. Genes unique to C. mellificae, including those of possible bacterial origin, were annotated based on function and include genes putatively involved in carbohydrate metabolism. This draft genome will facilitate additional investigations of the impact of C. mellificae infection on honey bee health and provide insight into the evolution of this unique family.